Melanocyte Function and Count of Leukotrichia in Vitiligo Using S100 Immunohistochemistry and Microphtalmia Associated Transcription Factor (MITF) - M. Yulianto Listiawan; Marina Rimadhani; Willy Sandhika (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Melanocyte of the hair follicle is one of the major sources of repigmentation in vitiligo. Leukotrichia is complete depigmentation with significant bleaching hair. Leukotrichia in nonsegmental vitiligo may contribute to the lack of response to medical treatment. Leukotrichia is often associated with absent of melanocyte, showing poor prognosis for vitiligo treatment. Purpose: To evaluate melanocyte count and function of leukotrichia’s melanocyte in vitiligo and comparing with other feature. Method: Melanocyte count in each feature of lesional skin in 18 segmental vitiligo patients were evaluated based on vitiligo extent tensity index (VETI). Melanocyte count has been evaluated using immunohistochemistry S100 and microphtalmia associated transcription factor (MITF). Results: Eighteen patients were nonsegmental vitiligo, and five of them had leukotrichia. Two of five leukotrichia patients did not express MITF nor melanocyte. There were no differences of melanocyte and MITF expression between patient with or without leukotrichia. Conclusion: Leukotrichia is a poor indicator for treatment response in vitiligo, but this research showed that leucotrichia may not contribute to the lack of response upon medical treatment.